The Impact of Organizational Communication on Job Satisfaction and Work Productivity at The Bappelitbangda Office of Barru Regency - Fitrisandi, Fitrisandi; Yusmanizar, Yusmanizar; Ferdiansyah, Rahmat (Syntax Corporation, 2025)
This study aims to analyze and explain the influence of organizational communication on job satisfaction and work productivity. In addition, this study aims to analyze and explain the influence of job satisfaction on work productivity. The method used in this study is quantitative data analysis with a general regression approach. This study involved 34 employees at the Bappelitbangda Office, Barru Regency. The research data used a questionnaire with a scale of 1–5 using a combination of negative and positive statements. Data analysis used linear regression analysis to prove the hypothesis that had previously been tested for validity, reliability, and classical assumptions. The results showed that the t-value of the organizational communication variable (X) was 5.392 > 1.6909 with a significance value of 0.000 <0.05, so H1 was accepted that organizational communication (X) had a positive and significant effect on job satisfaction (Y1) of employees at Bappelitbangda, Barru Regency, by 47.6%. The t-value of the organizational communication variable (X) is 3.935 > 1.6909 with a significance value of 0.000 < 0.05, indicating that H2 is accepted, namely that organizational communication (X) has a positive and significant effect on the work productivity (Y2) of employees at Bappelitbangda Barru Regency by 32.6%. If the t-value of the job satisfaction variable (Y1) is 4.296 > 1.6909 with a significance value of 0.000 < 0.05, then H3 is accepted, namely that job satisfaction (Y1) has a positive and significant effect on work productivity (Y2) of employees at Bappelitbangda Barru Regency by 36.6%.